DOI: 10.3990/1.9789036551137
|View full text |Cite
|
Sign up to set email alerts
|

Energy-based modeling and control of interactive aerial robots

Abstract: dr. A. FranchiThis dissertation has been approved by: prof.dr.ir. S. Stramigioli, Promotor dr.ir. F.P. Schuller, Co-promotor Copyright© 2020, by Ramy Rashad, Enschede, The Netherlands. All rights reserved. No parts of this thesis may be reproduced, stored in a retrieval system or transmitted in any form or by any means without permission of the author.x mogelijk om een verbeterde energiebewuste impedantie regelaar te ontwikkelen die gebruik maakt van concepten van energieroutering en energietanks. Ten slotte, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Publication Types

Select...
2
1
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 247 publications
(460 reference statements)
0
7
0
Order By: Relevance
“…This alternative view of dynamical systems have proven very effective for modeling, analysis and control purposes within the framework of port-Hamiltonian systems. The interested reader in this topic can refer to [8,22,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This alternative view of dynamical systems have proven very effective for modeling, analysis and control purposes within the framework of port-Hamiltonian systems. The interested reader in this topic can refer to [8,22,27].…”
Section: Discussionmentioning
confidence: 99%
“…By substituting equations (22,25,26) into ( 24) and expressing all quantities related to the child body in {p} using (15)(16)(17)(18), one can express the wrench W p,p c applied by the child on the parent as…”
Section: Parent-child Relationsmentioning
confidence: 99%
“…The pair (W b , T b ) define the power port by means of which the rigid body can be interconnected to other systems to compose a bigger dynamical system. For more details on this pH representation of rigid body motion and its derivation using Lie-Poisson reduction, the reader is referred to [23,25].…”
Section: Discussionmentioning
confidence: 99%
“…3)×se(3) represent the flow and effort variables of the energy storage subsystem, respectively. It can be shown that [25,23,24]…”
Section: Port-hamiltonian Model Of the Rigid Bodymentioning
confidence: 99%
“…where all symbols are defined in Table I. The MAV's equations of motion (1-3) can be reformulated in the port-Hamiltonian framework as the explicit dynamical system [6,37]:…”
Section: A Flying-end Effectormentioning
confidence: 99%